2021
DOI: 10.1097/ijg.0000000000001964
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Systemic Vascular Risk Factors Are Associated With Low-Tension Glaucoma

Abstract: Précis: Multiple systemic vascular-associated conditions including systemic hypertension and hypotension, diabetes mellitus, migraine headache, peripheral vascular disease, Raynaud syndrome, and anemia were associated with low-tension glaucoma.Purpose: The purpose of this study was to identify systemic risk factors associated with low-tension glaucoma.Patients and Methods: A retrospective case-control study design was employed to identify patients seen at the Mayo Clinic Department of Ophthalmology between 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Multiple vascular risk factors including systemic hypotension and hypertension, diabetes mellitus, peripheral vascular disease, Raynaud syndrome, and migraine headache have been shown to be associated with NTG. 10 The vascular theory of glaucomatous optic neuropathy (GON) in NTG considers it as a consequence of insufficient blood supply due to risk factors that reduce ocular blood flow and ocular perfusion pressure, leading to RGC death. 30 Here, we propose an additional alternate mechanism to explain how vascular factors may contribute to the pathogenesis of NTG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple vascular risk factors including systemic hypotension and hypertension, diabetes mellitus, peripheral vascular disease, Raynaud syndrome, and migraine headache have been shown to be associated with NTG. 10 The vascular theory of glaucomatous optic neuropathy (GON) in NTG considers it as a consequence of insufficient blood supply due to risk factors that reduce ocular blood flow and ocular perfusion pressure, leading to RGC death. 30 Here, we propose an additional alternate mechanism to explain how vascular factors may contribute to the pathogenesis of NTG.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that non-IOP factors, including vascular and cerebrospinal fluid (CSF) factors, may play significant roles in the development of NTG. 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, RNFL defects have been associated with vascular disease, in particular multiple RNFL defects has been linked to hypertension, end‐stage renal disease and cerebrovascular disease 29,30 . Various systemic vascular‐related conditions, including diabetes and hypertension have also been associated with low tension glaucoma 31,32 . We explored the notion that vascular wedge defects may be attributable to systemic vascular disease (self‐reported hypertension and diabetes) however since no statistical relationship was found, we have no reason to suggest that they were not glaucomatous in origin.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Various systemic vascular-related conditions, including diabetes and hypertension have also been associated with low tension glaucoma. 31,32 We explored the notion that vascular wedge defects may be attributable to systemic vascular disease (self-reported hypertension and diabetes) however since no statistical relationship was found, we have no reason to suggest that they were not glaucomatous in origin.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, glaucoma was responsible for 11% of all cases of blindness globally in adults aged ≥ 50 years ( 3 ). Some studies ( 4 6 ) have suggested that migraine increases the risk of developing glaucoma. However, there have been studies reporting no such findings ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%